The legend of Korra : turf wars. Part three - DiMartino, Michael Dante (Dark Horse Books, 2018)
"When Asami is kidnapped, Korra sets out to the Spirit Wilds to find her. Now teeming with dark spirits influenced by the half spirit-half human Tokuga, the landscape is more dangerous than ever before. The two women must trust in each other and work together if they are to make it out alive"--